Latent Growth in Self‐Regulatory Subdimensions in Relation to Adjustment Outcomes in Youth Aged 12–19. (20th February 2020) - Memmott‐Elison, Madison K.; Moilanen, Kristin L.; Padilla‐Walker, Laura M.
Abstract : This study assessed latent growth in behavioral inhibition, anger regulation, and goal‐setting from ages 12 to 18, as well as links between latent growth and depression, externalizing behavior, and prosocial behavior at age 19. A second goal included examining whether latent growth in these constructs and associations with distal outcomes varied by sex. Generally speaking, self‐regulatory subdimensions displayed distinct patterns of developmental growth from ages 12 to 18. Growth in self‐regulatory subdimensions did not vary by sex, though initial levels of anger regulation and goal‐setting did vary by sex. In addition, self‐regulatory subdimensions from ages 12 to 18 were differentially related to adjustment outcomes at age 19. However, sex did not moderate associations between growth in self‐regulatory subdimensions and distal outcomes.